THE SHIFT OF THEMES AND RHEMES IN THE TRANSLATION OF ENGLISH POLITICAL TEXTS INTO INDONESIAN - Widya Astuti; Rahmad Husein; Syahron Lubis (Universitas Negeri Medan, 2019)
This study was conducted to describe the shift of themes and rhemes in The Translation of English Political Text into Indonesian. In this research, descriptive qualitative design is applied by the researcher in order to answer the questions. The data were taken from English and Indonesia political news texts of Waspada. The technique used was interactive model by Miles, Huberman and Saldana (2014). This study found some enrichment with variation of theme and information structure of thematic and rhematic in English – Indonesia Waspada political texts. Based on analyzing data, the findings of this study are formulated : (1) There are some ways in which shifts applied in the thematic and rhematic in English - Indonesian translation of Waspada political texts there are such as : the SL which is differently translated into TL considering the grammatical pattern of both language and the unit of word constructing the theme and rheme and (2) There are some reasons for applying shifts in the thematic and rhematic shift in English – Indonesian translation of Waspada political texts such as different language system and grammatical structure from both English and Indonesia. Keywords: Translation Shifts, Theme, Rheme, Political, Text